2022
DOI: 10.47280/revfacagron(luz).v39.n1.15
|View full text |Cite
|
Sign up to set email alerts
|

Identification and morphological characterization of marine actinomycetes as biocontrol agents of Fusarium solani in tomato

Abstract: Fusarium spp. damages the roots of crops, its control is with synthetic fungicides, however, marine actinomycetes can be an option to the use of agrochemicals. The objective of this work was the identification and morphological characterization of marine actinomycetes as antagonists to Fusarium solani (Mart.) Sacc. Fusarium spp. was isolated from diseased tomato plants and mangrove sediment actinomycetes, both identified through taxonomic keys and molecular techniques. Eight isolates of Fusarium spp. were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…isolates as well as in colony diameter. Our results mirror the findings reported by Torres-Rodriguez et al (2022a), who found morphological differences in color, diameter, and type of mycelium among F. solani isolates. Diversity was also reflected in reproduction structures, such as macroconidia, microconidia, and chlamydospores, with differences among the obtained isolates, indicating the possible existence of different species within the Fusarium genus.…”
Section: Discussionsupporting
confidence: 92%
“…isolates as well as in colony diameter. Our results mirror the findings reported by Torres-Rodriguez et al (2022a), who found morphological differences in color, diameter, and type of mycelium among F. solani isolates. Diversity was also reflected in reproduction structures, such as macroconidia, microconidia, and chlamydospores, with differences among the obtained isolates, indicating the possible existence of different species within the Fusarium genus.…”
Section: Discussionsupporting
confidence: 92%
“…And N. lucentensis , inhibited the mycelial growth of F. solani by 72 and 68%, respectively, and Streptomyces sp. showed no significant differences with the synthetic fungicide [ 67 ].…”
Section: Antifungal In Vitro Activity Of Actinomycetes Isolated In Di...mentioning
confidence: 99%
“… Antifungal activity (% growth inhibition * ) in vitro of actinomycetes isolated from different environments [ 1 , 3 , 4 , 6 , 10 , 19 , 20 , 21 , 53 , 59 , 60 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. …”
Section: Figurementioning
confidence: 99%
“…Actinomycetes could be utilized as a biological control agent against plant pathogens. Actinomycetes are known to be capable of reducing pathogen activities, such as inhibitory activity of mycelial growth of B. cinerea on tomatoes by 52.38% to 96.19% (Lahmyed et al, 2021); in vitro inhibition up to 85% hyphal desegregation, and antibacterial activity against soilborne-pathogens on Solanum lycopersicum and Daucus carota (Djebaili et al, 2021); development suppression of Alternaria brassicicola on cabbage with increases of ≥80% protection level compared to control (Hassan et al, 2017); reduce damping-off incidence of Pythium aphanidermatum in cucumber by up to 71% (Costa et al, 2013); and inhibit mycelial growth of Fusarium solani by up to 70% (Torres-Rodriguez et al, 2022). These pathogen suppressing activities are caused by their ability to produce several enzymes, i.e., amylase, protease, cellulase, chitinase, esterases, and lecithinase (Loliama et al, 2013;Lahmyed et al, 2021;Zulfa et al, 2021;Díaz-Díaz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies related to the use of Streptomyces as a biocontrol agent include: the use of Streptomyces to inhibit Ganoderma sp. (Zulfa et al, 2021), Alternaria brassicicola on cabbage seedlings (Hassan et al, 2017), charcoal rot disease on cowpea and mungbean (Jaber & Fayyadh, 2019), damping-off disease in cucumber (Costa et al, 2013), Macrophomina phaseolina and Rhizoctonia solani on Phaseolus vulgaris (Díaz-Díaz et al, 2022), Fusarium solani from tomato (Torres-Rodriguez et al, 2022), etc. In contrast, there is currently relatively little research on actinomycetes from Indonesia.…”
Section: Introductionmentioning
confidence: 99%